Implementation of Discovery Learning Model to Improve Student Learning Outcomes in Fiqh Learning at MI Al-Fatah Manggarai Barat - Mulyadi, Musni; Zubaedi, Muhammad (Journal of Indonesian Primary School, 2025)
This study aims to improve learning outcomes in the subject of Fiqh with the Discovery Learning Learning Model for fourth grade students at MI Al-Fatah Manggarai Barat in 2024, this type of research uses Classroom Action Research, consisting of four stages, namely; planning, action, observation, reflection. The subjects of the study were 20 fourth grade students at MI Al-Fatah Manggarai Barat. The data collection method used observation, documentation, testing and interview methods. The results of this study showed a significant increase in students' critical and collaborative thinking. The percentage of students' critical thinking in the pre-cycle was 48%, cycle I was 65%, Cycle II meeting I increased to 85%, Cycle III increased to 95%. Student learning outcomes obtained in cycle I were 84.55%, but in cycle II it became 89.25%, Cycle III the application of Discovery Learning was increased again so that the percentage obtained increased to 97.55%. The application of the Discovery Learning model can improve Learning Outcomes by making modifications in terms of; use of interesting media, seating arrangements, and effective classroom management strategies.